Case Report: Solitary metastasis to the appendix after curative treatment of HCC - Zhang, Zun-Yi; Wang, Yu-Wei; Zhang, Wei; Zhang, Bi-Xiang (Frontiers in Surgery, 2023)
Background Liver cancer is now the fourth most common cancer in China. The most important factor in decreasing the overall survival is recurrence. Nearly 40%–70% of patients would be detected with intrahepatic or extrahepatic recurrence in 5 years after R0 resection. The intestine is not a usual site for extrahepatic metastasis. Only one case of hepatocellular carcinoma (HCC) metastasis to the appendix has been reported so far. So, it poses a difficulty for us to develop treatment plan. Case presentation Here, we report a very rare case of a recurrent HCC patient. R0 resection was first performed on this 52-year-old men who was diagnosed with Barcelona Clinic Liver Cancer stage A HCC. Different from other cases, a solitary metastasis to the appendix was detected 5 years after the R0 resection. After discussing with the multidisciplinary team, we decided to perform surgical resection again. The final postoperative pathology confirmed HCC. Complete responses were detected in this patient after the combined treatment of transarterial chemoembolization, angiogenesis inhibitors, and immune checkpoint inhibitors. Conclusion Because solitary metastasis to the appendix in HCC is very rare, this case might be the first reported in HCC patients after R0 resection. This case report highlights the efficacy of the combination of surgery, local regional therapy, angiogenesis inhibitors, and immune treatment in HCC patients with solitary metastasis to the appendix.